POTENSI PRODUKSI HIJAUAN PADA PASTURA ALAMI DI PULAU SAMOSIR KABUPATEN SAMOSIR - Hanafi, Nevy D. (Jurnal Online Pertanian Tropik, 2017)
Samosir island has potential ruminant livestock development include beef cattle, buffaloes, goats and horses. This study aims to determine the potential of the forage production on natural pastures in Samosir, Samosir regency. Research carried on in Samosir in July to October 2016. Assessment of Forage Feed on pasture land in Samosir includes determining the locations of the study based on altitude, sampling forages and forage calculate productivity. Location of the study amounted to 15 points, at an altitude of 905-1200 meters above sea level there are nine (9) research sites that Simbolon, Simanindo, Unjur, Garoga, Marlumba, Suhisuhi Dolok, Parbaba Dolok, Onan Runggu, Sabungan Nihuta. While at an altitude up 1200 m above sea level, there are 6 locations including research Tanjungan, Sidihoni, Lintong Sunut, Desa Lumban Simbolon, Sipira 32, dan Sipira 33. The results showed that the fresh Production of highest at an altitude 905-1200 meters above sea level was 2.048,27 kg/ha/harvest, and production dry matter is 814,43 kg/ha/harvest. Temporarily the mean production of fresh ingredients at an altitude up 1200 m above sea level is 1.696,1 kg/ha/harvest and production dry matter is 739,28 kg/ha/harvest. Conclusion altitude on pasture gives effect to the production of fresh and dry matter forage.